The Cold War in the Classroom International Perspectives on Textbooks and Memory Practices - Christophe, Barbara; Gautschi, Peter; Thorp, Robert (Palgrave Studies in Educational Media, 2019)
Education; Teaching; Education-History; Communication; Russia-History; Europe, Eastern-History; Historiography